71.6k views
3 votes
Help please, if you know how to do it. Posting separate questions so you get more points,l thanks

Help please, if you know how to do it. Posting separate questions so you get more-example-1
Help please, if you know how to do it. Posting separate questions so you get more-example-1
Help please, if you know how to do it. Posting separate questions so you get more-example-2
User Peenut
by
5.0k points

2 Answers

5 votes

Answer:

9514 1404 393

y = x^2 +x +1; (-1/2, 3/4)

y = 3x^2 -15x +12; (-2, 54), (5, 12)

y = -1/2x^2 +2x +5; (0, 5)

1. The graph looks like the vertex is at x = -1/2. So we can start with the equation y = (x +1/2)^2 +k. At x=0, this becomes 1 = 1/4 +k, or k = 3/4. The leading coefficient of 1 is consistent with the other points shown, so the equation is ...

y = (x +1/2)^2 +3/4 . . . . vertex is (-1/2, 3/4)

y = x^2 +x +1

User Esgaldir
by
5.5k points
5 votes

9514 1404 393

Answer:

  1. y = x^2 +x +1; (-1/2, 3/4)
  2. y = 3x^2 -15x +12; (-2, 54), (5, 12)
  3. y = -1/2x^2 +2x +5; (0, 5)

Explanation:

1. The graph looks like the vertex is at x = -1/2. So we can start with the equation y = (x +1/2)^2 +k. At x=0, this becomes 1 = 1/4 +k, or k = 3/4. The leading coefficient of 1 is consistent with the other points shown, so the equation is ...

y = (x +1/2)^2 +3/4 . . . . vertex is (-1/2, 3/4)

y = x^2 +x +1

__

2. The zeros appear to be at x=1 and x=4, so the factored form of the equation is ...

y = a(x -1)(x -4)

At x = 0, this is ...

12 = a(-1)(-4)

3 = a

So, the equation is ...

y = 3x^2 -15x +12

The values at the two points of interest are ...

y = 3(-2-1)(-2-4) = 54 . . . . point (-2, 54)

y = 3(5 -1)(5 -4) = 12 . . . . point (5, 12)

__

3. Using the vertex shown, the vertex form of the equation is ...

y = a(x -2)^2 +7

Filling in the point (-2, -1), we can find the value of a:

-1 = a(-2-2)^2 +7

-8 = 16a

a = -8/16 = -1/2

So, the equation is ...

y = -1/2x^2 +2x +5

For x=0, the y-value is 5. The y-intercept is (0, 5).

User Digijay
by
5.1k points